LAYANAN INFORMASI OLEH GURU PEMBIMBING TENTANG TUGAS PERKEMBANGAN REMAJA SISWA KELAS X SMA NEGERI 9 PONTIANAK - Pratiwi, Indah; Astuti, Indri; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to obtain information services about the tasks of the development of adolescent class X students SMA Negeri 9 Pontianak. The research method used is descriptive method with quantitative approach and use survey research form. The population that became the source of data in this study were all students of class X with a population of 244 learners with a sample of 61 respondents. Based on the results of data analysis shows Information Service tasks Youth Development by Teachers BK on Class X Students SMA Negeri 9 Pontianak get the value 85, 24% which is in the category of